Hospitalisation and surgery: Is exposure associated with increased subsequent depressive symptoms? Evidence from The Irish Longitudinal Study on Ageing (TILDA) - Kenny, Rose; Scarlett, Siobhan (My University, 2018)
Background: The dramatic shift in the global population demographic has led to increasing numbers of older people undergoing hospitalisation and surgical procedures. While necessary, these exposures may lead to an increase in depressive symptoms. Objectives: To determine whether hospitalisation or hospitalisation with surgery under general anaesthesia is associated with an increase in depressive symptoms in adults over the age of 50. Methods: Depressive symptoms were assessed using the Center for Epidemiologic Studies Depression Scale in 8036 individuals at waves 1 and 2 of The Irish Longitudinal Study on Ageing (TILDA), 2 years apart. Mixed-effects models were used to investigate the hypothesis after adjustment for risk factors for depression and potential confounders. Results: During the 12 months preceding wave 1, a total of 459 participants were hospitalised (mean age, 67.0; 55.3% female), and a further 548 participants (mean age, 64.6; 51.8% female) were hospitalised and underwent surgery with general anaesthesia; 6891 (mean age, 63.5; 54.3% female) were not hospitalised. Analysis of waves 1 and 2 data using mixed-effects models demonstrated that there was a 7% increased adjusted incidence rate of depressive symptoms (IRR [95% CI] = 1.07 [1.02-1.11]) in the Center for Epidemiologic Studies Depression Scale in the hospitalisation group and a 4% increased adjusted incidence rate of depressive symptoms (IRR [95% CI] = 1.04 [1.00-1.08]) in the surgery group compared with those with no hospitalisation. Conclusion: Hospitalisation and hospitalisation with surgery and general anaesthesia are associated with increased depressive symptoms. This is the first time a longitudinal population-representative study has demonstrated this relationship for both exposures simultaneously.
PUBLISHED
Keywords: depression, depressive symptoms, hospitalisation, low mood, surgery; Ageing